Fruit Breeding - Badenes, Maria Luisa; Byrne, David H. (Handbook of Plant Breeding, 2012)
Fruit Breeding is the eighth volume in the Handbook of Plant Breeding series. Like the other volumes in the series, this volume presents information on the latest scientific information in applied plant breeding using the current advances in the field, from an efficient use of genetic resources to the impact of biotechnology in plant breeding. The majority of the volume showcases individual crops, complemented by sections dealing with important aspects of fruit breeding as trends, marketing and protection of new varieties, health benefits of fruits and new crops in the horizon. The book also features contributions from outstanding scientists for each crop species. Maria Luisa Badenes Instituto Valenciano de Investigaciones Agrarias (IVIA), Valencia, Spain David Byrne Department of Horticultural Sciences, Texas A&M University, College Station, TX, USA.